Stories of Change - Rwanda, Final Report - Iruhiriye, Elyse; Olney, Deanna K.; Ramani, Gayathri V.; Heckert, Jessica; Niyongira, Emmanuel; Frongillo, Edward A. (International Food Policy Research Institute, 2019)
Globally, undernutrition is related to almost half of the deaths in children younger than five years of age. It leads to large human and economic costs to countries through increased morbidity and mortality in childhood, poor child growth and development, and hinders adult work capacity and productivity. These consequences, in turn, have serious implications for national development. Eliminating malnutrition has, therefore, been on the forefront of the political agenda of many countries worldwide and for global movements such as Scaling Up Nutrition (SUN). Extensive evidence on what nutrition-specific interventions work to reduce malnutrition exists. Less is known, however, about how to effectively implement these interventions at scale, and what mix of interventions is needed to effectively address the multiple co-existing nutrition problems in different contexts (including nutrition-sensitive programs). Additionally, greater clarity is needed on the role that commitment, program and policy coherence, and context-specific factors, play in creating enabling environments to reduce malnutrition. The Stories of Change (SoC) case studies, originally conducted in Bangladesh, Ethiopia, India (Odisha state), Nepal, Senegal, and Zambia, and now in Rwanda, aim to fill some of these knowledge gaps by examining the “drivers of change” in reducing malnutrition across different contexts.